Effects of Guided Self-Reflection on Students with ESL Learning Difficulties - Oo, Pou San; Choy, S. Chee (INTI University College, 2009)
This paper alms to investigate the effect of guided self-reflection on students with ESL learning difficulties. The data was obtained from a total of eight respondents who were asked to voluntarily undergo a series of guided self-reflection sessions by a student counsellor. The respondents were selected after administering a teacher made test for English among 57 students who enrolled for courses in an institution of higher learning In Malaysia. The analysis of the responses to the interviews was done using the process of topic ordering to describe the process of preparing qualitative data for analysis. Using this process the transcripts were analyzed inductively. It was found that students benefited from the counselling sessions based on the Improvement In the test scores. The study also highlighted certain perceptions low achieving students have of themselves which could influence the strategies they used to learn English. The home and social environments could also play a significant role in this.